2019
DOI: 10.1109/access.2019.2901903
|View full text |Cite
|
Sign up to set email alerts
|

Quickly Obtaining Range of Articulated Rotating Speed for Electrically Driven Large-Load-Ratio Six-Legged Robot Based on Maximum Walking Speed Method

Abstract: The articulated rotating speed is one of the important parameters to determine the drive devices and actuating devices of joints for legged robots. Compared with the small-scale multi-legged robots, the range of the output speed of the joint should be as accurate as possible for the large-load-ratio multi-legged robots. To reasonably select the devices of joints, the maximum walking speed method is proposed to quickly and accurately obtain the range of articulated rotating speed by taking an electrically drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In order to facilitate the theoretical analysis of the algorithm, this article takes the mathematical model of the four-wheel mobile robot as an example, as shown in Figure 6. The front and rear wheelbase of the robot is L. The distance between the midpoint of the wheel and the midpoint of the robot system is d, as shown in Equation (17). The motion direction angle of the robot is θ.…”
Section: Robot System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to facilitate the theoretical analysis of the algorithm, this article takes the mathematical model of the four-wheel mobile robot as an example, as shown in Figure 6. The front and rear wheelbase of the robot is L. The distance between the midpoint of the wheel and the midpoint of the robot system is d, as shown in Equation (17). The motion direction angle of the robot is θ.…”
Section: Robot System Modelmentioning
confidence: 99%
“…Under the nonholonomic constraints, the external distributed sensor method was applied. The finite-time convergence problem of multi-robot cooperative control was studied [16,17]. The motion consistency problem of complex multi-robots was studied, and the dynamic formation of multi-mobile robots was realized by designing a distributed formation control law [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Equations (3), (10), and (11), the total articulated torques of the support leg s k can be respectively acquired for the torque ( )…”
Section: Jqmentioning
confidence: 99%
“…•3• ATHLETE [7], Dante II [8], and so on, Zhuang et al [9][10][11] concluded that the main characteristics of the large-load-ratio legged robots roughly included the larger body mass, bigger body size and large load ratio than the conventional legged robots. The independent energy supply units necessarily need to be carried when the working environment of large-load-ratio legged robots is changed from the laboratory to the outdoor.…”
Section: Introductionmentioning
confidence: 99%